FPGA controlled five level soft switching full bridge DC-DC converter for high power applications. Issue 1 (31st December 2016) - Sivavara Prasad, J.; Obulesh, Y.P.; Sai Babu, Ch.
Abstract: The objective of the paper is to develop soft switching for the novel five level full bridge DC-DC converter for high power applications. The use of conventional DC-DC converter is likely to decrease the efficiency because of the hard switching, which generates losses during the switch on/off. This paper mainly deals with the development of zero voltage and zero current switching for five level full bridge DC-DC converter. The proposed topology will provide five level DC-DC output voltage, thereby the size of filter in both input and out sides will get reduced as compared to the existing topologies. By increasing the voltage levels, the stress across each switch and DC filter in the rectifier side will get reduced. Only eight switches are used for generating five levels in the proposed converter topology which reduces cost and also total switching losses, thus improves the overall efficiency of a system and it is very much suitable for high power DC-DC applications. The control signals for the proposed converter are developed from the Field Programmable Gate Array. The simulation and experimental results are presented for prototype model of 500 W.